On Robustness of Usual Confidence Region under Transformation Misspecification - YANG, Zhenlin (Institutional Knowledge at Singapore Management University, 1998)
Studies robustness of confidence region for linear model parameters following a misspecified transformation of dependent variable. Confidence region after transformation specification; Effect of a priori misspecification of a transformation; Effect of data-based misspecification of a transformation.